The Correlation Between Immune Invasion and SARS-COV-2 Entry Protein ADAM17 in Cancer Patients by Bioinformatic Analysis - Wang, Kai; Deng, Haoyue; Song, Binghui; He, Jiayue; Liu, Shuguang; Fu, Jiewen; Zhang, Lianmei; Li, Dabing; Balaji, Kyathegowdanadoddi Srinivasa; Mei, Zhiqiang; Cheng, Jingliang; Fu, Junjiang (Frontiers in Immunology, 2022)
SARS-Cov-2 caused the COVID-19 pandemic worldwide. ADAM17 functions as a disintegrin and transmembrane metalloproteinase domain protein involved in the regulation of SARS-CoV-2 receptor ACE2. However, its impact on cancer patients infected with COVID-19 and its correlation with immune cell infiltration is unclear. This study compared ADAM17 expression between normal and tumor tissues based on GEPIA. The correlations between ADAM17 expression and immune cell infiltration and immunomodulators were investigated. Besides, treated drugs for targeting ADAM17 were searched in the TISDB database. We found that ADAM17 was highly conserved in many species and was mainly expressed in lung, brain, female tissues, bone marrow and lymphoid tissues. It was also highly expressed in respiratory epithelial cells of rhinitis and bronchus. ADAM17 expression in tumors was higher than that in several paired normal tissues and was negatively correlated with the prognosis of patients with malignant tumors. Interestingly, ADAM17 expression significantly correlated with immunomodulators and immune cell infiltration in normal and tumor tissues. Moreover, eight small molecules targeting ADAM17 only demonstrate therapeutic significance. These findings imply important implications for ADAM17 in cancer patients infected with COVID-19 and provide new clues for development strategy of anti-COVID-19.